Carbon Storage in Cold Temperate Ecosystems in Southern Patagonia, Argentina. - Peri, Pablo Luis (inTech, 2022)
Recently there has been an increasing interest of research related to improve the understanding of carbon (C) sequestration mainly under Article 3.4 of the Kyoto Protocol of the United Nations Framework Convention on Climate Change where countries can count this sequestration as a contribution to reduce greenhouse gas emission (IPCC, 2001). Data on C storage in forests, grasslands and shrublands are essential for understanding the importance of rapidly increasing level of CO2 in the atmosphere and its potential effect on global climate change. In South America, mean annual temperature is predicted to increase by 3-4 °C in both summer and winter between 30° and 55° SL (Manabe & Wetherald, 1987). Such an increase would have significant effects on Patagonian ecosystems. In this context, secondary indigenous forests are considered efficient C sink ecosystems. Nothofagus antarctica (ñire), one of the main deciduous native species in the Patagonian region (Argentina), covers 751.643 hectares over a wide latitudinal (from 36° 25' to 54° 53' SL) and altitudinal (near sea level to 2000 m.a.s.l.) distribution. These forests occur naturally in different habitats such as poorly drained sites at low elevations, exposed windy areas with shallow soils, depressions under cold air influence, or in drier eastern sites near the Patagonian steppe (Veblen et al., 1996). These forests provide a range of wood products including poles, firewood and timber for rural construction purposes. Site quality for N. antarctica ranges from tall trees up to 15 m in dominant height on the best sites to shrubby trees of 2 m tall on rocky, xeric and exposed sites, and also in poorly drained sites. Previous research has highlighted the importance of stand age on the magnitude of C pools in both forest biomass and forest floor pools (Silvester & Orchard, 1999; Davis et al., 2003). Largescale canopy disturbance in N. antarctica forests may occur as a result of blowdown, snow avalanches or fire. This results in abundant regeneration (100,000 seedlings ha-1 less than 1m tall, up to 20 years of age) followed by self thinning due mainly to light competition resulting in a final stand density of 200-350 trees ha-1 at mature stages (more than 180 years of age). It is important to emphasize that many researchers have only focused on aboveground carbon sequestration (Davis et al., 2003). However, roots in forest ecosystems can contribute up to two times more biomass than above-ground components in young growth phases (Peri et al., 2006, 2008). There are few studies of above- and below-ground pools of C storage in Patagonian Nothofagus forests that provide an understanding about ecosystem functionality (Peri et al., 2004, 2005) and the consequences of different disturbance and management regimes. In this context, forest ecosystem pools and fluxes of C are strongly affected by forest management (Finér et al., 2003). Peri et al. (2010) showed that C storage in tree components (leaves, stems, branches, roots) and forest floor change as a result of different forest structure determined by the proportion of crown classes, development stages (age) and the site quality where trees grow. The steppe ecosystem, mainly characterised by the presence of tussock, short grasses and shrubs, covers 85% of the total area. Grazing has modified the structure of Patagonian ecosystems by reducing vegetation cover, increasing bare areas, and changing floristic composition. Erosion and degradation processes have occurred in several areas of Patagonia due to an overestimation of the carrying capacity of these rangelands, inadequate distribution of animals in very large and heterogeneous paddocks, and year-long continuous grazing (Golluscio et al., 1998). In Patagonia, most of the actual knowledge about the environmental factors that affect net primary production of grasslands at regional level derives from the importance of mean annual precipitation, radiation and temperature (Jobbágy & Sala, 2000). However, data on C accumulation in both above- and belowground components of plant functional types are essential for evaluating the impacts of grazing on C cycle and long -term effects on the C balance of grasslands. Global estimates of the relative amounts of C in different vegetation types suggest that grasslands approximately contribute more than 10% of the total biosphere store (Nosberger et al., 2000). Also, it has been demonstrated that most temperate grasslands under existing management conditions are considered to be C sink and sequester more C than arable crops (Connan et al., 2001). Therefore, the aim of this manuscript was to describe the amount of C in both above- and below-ground components for the main cold temperate ecosystems in Southern Patagonia (Argentina). In particular, the aim was to quantify the C storage in an age sequence and among crown classes for individual trees grown at different site qualities of deciduous N. antarctica forests in Southern Patagonia and under silvopastoral use, and to quantify the amount of C for main grassland steppe ecosystems including the effect of grazing.